Fintech's powerful function: Reducing gender income inequality - Li, Shu; Ghazali, Mohd Fahmi; Salleh, Masrina Nadia Mohd (The Economics and Finance Letters, 2025)
The innovation of financial technology (fintech) has significantly transformed the global financial landscape. Fintech's impact is particularly crucial for alleviating income inequality, as women facing gender-specific financial barriers experience enhanced economic opportunities through algorithm-based lending decisions and expanded digital access. Concurrently, the income disparity between men and women persists as a significant global challenge that researchers have extensively investigated. This study examines the relationship between fintech adoption and gender income inequality by analyzing provincial panel data from China spanning 2011 to 2021. Employing both Ordinary Least Squares (OLS) and Two-step Generalized Method of Moments (GMM) models, our findings reveal that fintech adoption measured by the breadth and depth of digital finance use and the level of financial inclusion digitization significantly reduces gender income inequality. This study provides a novel analysis demonstrating a significant negative relationship between fintech adoption and gender income inequality at the provincial level across all dimensions: the breadth, depth, and digitization of fintech. This suggests that Fintech serves not only as a transformative tool for the financial industry but also contributes significantly to socioeconomic equity. By evaluating the impact of digital financial services on gender economic outcomes, this research provides valuable implications to policymakers, financial institutions, and Fintech product developers promoting fintech and gender equality. Based on these findings, we recommend promoting fintech as an effective tool for advancing gender pay equity.